Pengaruh Stres Kerja Terhadap Kinerja Karyawan Pertolongan Kecelakaan Penerbangan Dan Pemadam Kebakaran (Pkp-Pk) Di Bandar Udara Internasional Adisutjipto Yogyakarta - Faturrahman; Eny Sri Haryati (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2023)
Along with the times, the number of air passengers in Indonesia is expected to grow 30% year-on-year to 140 million in the next few years, making Indonesia an important market for air passengers. So Indonesia is expected to become the world's sixth-largest air transportation market by 2034 (Ministry Industry of the Republic of Indonesia, 2022). ARFF (Airport Rescue and Fire Fighting) is a unit part of and rescue at an airport that plays a very important role. Therefore, it is necessary to monitor the level of employee work stress, and it is hoped that employees will feel encouraged to work so that the impact on the performance of ARFF employees can increase and be better. This study aims to determine whether there are the effect of job stress on employee performance ARFF (Airport Rescue and Fire Fighting) at Adisutjipto International Airport Yogyakarta and how much influence it has. The research method used is a quantitative method, namely by using population and sample of all employees ARFF (Airport Rescue and Fire Fighting) at Adisutjipto International Airport Yogyakarta as respondents. The data collection technique used is by including a number of theoretical foundations, documentation, observation and distributing questionnaires/surveys. Then the data analysis technique uses the application program tool SPSS (Statistical Package for the Social Sciences) version 26. The results of this study are known to be a constant value of 64.654 and a regression coefficient of -0.116, so the linear regression equation is Y = 64.654 - 0.116 X. Then it is known that the value (Sig.) is 0.428 > 0.05 and the value of t count -0.807 < t table 2.064. And the coefficient of determination R2 (R Square) of 0.026 or 2.6%. So it can be concluded that Job Stress (X) has a negative effect and contributes 2.6%, the remaining 97.4% is influenced by other factors not examined in this study. However, there is no significant effect on Employee Performance (Y) ARFF (Airport Rescue and Fire Fighting) at Adisutjipto International Airport Yogyakarta.